Perencanaan Strategi Sistem Informasi Dengan Metode Ward And Peppard di Perusahaan Toko Surabaya cabang Surakarta - Adiatama Cahyo; Augie David Manuputty (Journal of Information System and Informatics, 2021)
The role of information technology is very important for the progress of a company, by using information technology, strategic planning for the company's development will be better, some companies will definitely take advantage of information technology for the progress of their companies, this is also used for Toko baju Surabaya cabang Surakarta. This shop is a company engaged in the sale of clothing, this company uses the SmartConsole application to support sales. However, there are still sectors in this company that have not implemented an information system, one of which is in the section on stock data collection and payroll. Therefore, an appropriate IS / IT strategic planning is needed. This research was conducted using the Ward and Peppard method with SWOT analysis, Five Forces Porter, and McFarlan Strategic Grid. The output produced from this study is in the form of strategic recommendations from the results of the internal and external environmental analysis of the company's information system, as well as a proposal for an Information System to be mapped using the McFarlan Strategic Grid to be applied to companies in the next two years.